Journey to Mastery: Understanding the Lived Experiences of Novice English Teachers in Handling Practical Research Subject in Senior High School - Lizaso, Jeramee Tecson; Shienna Marie Caparas (Researchparks Publishing, 2025)
Teaching is a professional and dynamic calling that demands not only pedagogical content knowledge but also the capacity to identify and apply recent methods based on evidence-based research activities. Practical research is an applied course in the K to 12 senior high school curriculum that equips students with basic inquiry, analysis, and academic writing skills. This study explored the lived experiences of novice English teachers tasked to handle Practical Research subject in senior high schools in Santa Rosa, Laguna. These teachers have been accorded limited training in research teaching, so they typically encounter many challenges, including inadequate preparation, inadequate resources, and managing multiple roles. This research aims to identify how these teachers perform their roles, manage challenges, and become involved in research despite being novices. Utilizing a qualitative phenomenological approach, data were collected through semi-structured interviews with ten (10) selected novice English teachers. Purposeful non-random sampling and snowball non-probability sampling were utilized to ensure the particular selection of the participants. Braun and Clarke’s thematic analysis was utilized and revealed ten (10) major themes, including limited research background, personal and institutional challenges, peer mentorship, and the demand for self-directed learning. Teachers indicated both motivation and hesitation was based on a sense of desire to serve students and professional growth, while others were overwhelmed and disinterested in continuing to teach research. Notwithstanding these mixed feelings, numerous teachers expressed resilience and a sense of commitment to continuous improvement. The research concluded that particular assistance, guidelines-oriented training, better facilities, and brief research guidelines were necessary to prepare novice teachers effectively. The findings also have implications for teacher development programs and education policy, especially in creating a supportive environment for research involvement and professional development.